2023
DOI: 10.3389/fpsyg.2023.982328
|View full text |Cite
|
Sign up to set email alerts
|

Leaders’ ambition and followers’ cheating behavior: The role of performance pressure and leader identification

Abstract: PurposeWe seek to understand why and how leaders’ actions that are positive from organizational perspectives, drive to engage employees in cheating behaviors.Design/methodology/approachThe proposed mediated moderation model was tested in two separate studies, study 1 and study 2, with data collected from police officers and employees of Islamic banking respectively, and then analyzed with Mplus for random coefficient models for direct effects, indirect effects, and for mediated moderation.FindingsIt was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…The rationale behind this is that performance pressure functions as a stressor, compelling individuals to invest psychological effort in managing this stressor to protect, develop, and maintain their cognitive resources (Trivedi and Pattusamy, 2022). In this context, FSB emerges as a job resource (Crans et al, 2022) within the JD-R framework, utilized by employees to cope with the demands imposed by performance pressure (Adeel et al, 2023). Additionally, as noted by Zhang et al (2022a), seeking feedback allows employees to gather information about their performance, identify areas for improvement, and make necessary adjustments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The rationale behind this is that performance pressure functions as a stressor, compelling individuals to invest psychological effort in managing this stressor to protect, develop, and maintain their cognitive resources (Trivedi and Pattusamy, 2022). In this context, FSB emerges as a job resource (Crans et al, 2022) within the JD-R framework, utilized by employees to cope with the demands imposed by performance pressure (Adeel et al, 2023). Additionally, as noted by Zhang et al (2022a), seeking feedback allows employees to gather information about their performance, identify areas for improvement, and make necessary adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Job Demands-Resources theory (JD-R) (Bakker et al, 2004), job demands refer to the aspects of a job that require sustained effort and are associated with physical, cognitive or emotional strain. Performance pressure can be considered a job demand (Adeel et al, 2023) as it involves high expectations, time pressure (Shalley and Perry-Smith, 2001) and the need to meet the required demanded output (Zhang et al, 2017). On the other hand, FSB can be viewed as a job resource (Crans et al, 2022) within the JD-R theory, which helps manage job demands.…”
Section: Igniting Work Innovationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the research analyzes the psychological mechanism through which the abusive behaviors of the supervisors affect the creative idea sharing of the employees. Research on abusive supervision has demonstrated that abusive supervisors leaves the subordinates more vulnerable to engage in cheating and other unethical counterproductive work behaviors [ 17 , 18 ]. This research also analyzes the mediating role played by cheating behavior in the association among abusive supervision as well as the creative idea-sharing behavior of the employees.…”
Section: Introductionmentioning
confidence: 99%